Sexually dimorphic RNA helicases DDX3X and DDX3Y differentially regulate RNA metabolism through phase separation - Shen, Hui; Yanas, Amber; Owens, Michael C; Zhang, Celia; Fritsch, Clark; Fare, Charlotte M; Copley, Katie E; Shorter, James; Goldman, Yale E; Liu, Kathy Fange (Molecular cell, 2022)
Sex differences are pervasive in human health and disease. One major key to sex-biased differences lies in the sex chromosomes. Although the functions of the X chromosome proteins are well appreciated, how they compare with their Y chromosome homologs remains elusive. Herein, using ensemble and single-molecule techniques, we report that the sex chromosome-encoded RNA helicases DDX3X and DDX3Y are distinct in their propensities for liquid-liquid phase separation (LLPS), dissolution, and translation repression. We demonstrate that the N-terminal intrinsically disordered region of DDX3Y more strongly promotes LLPS than the corresponding region of DDX3X and that the weaker ATPase activity of DDX3Y, compared with DDX3X, contributes to the slower disassembly dynamics of DDX3Y-positive condensates. Interestingly, DDX3Y-dependent LLPS represses mRNA translation and enhances aggregation of FUS more strongly than DDX3X-dependent LLPS. Our study provides a platform for future comparisons of sex chromosome-encoded protein homologs, providing insights into sex differences in RNA metabolism and human disease.